FRI0517 Vessel wall morphology in giant cell arteritis– a longterm sonographic follow-up study. (12th June 2018) - Schegk, E.; Berger, C.T.; Imfeld, S.; Staub, D.; Recher, M.; Kyburz, D.; Aschwanden, M.; Daikeler, T.
Abstract : Background: Ultrasound (US) is a cornerstone in the diagnosis of GCA. Only limited data on how US documented large vessel wall thickening changes during treatment is available. Objectives: To assess arterial vessel wall findings by US during long term follow-up in GCA patients with large vessel vasculitis (LVV) and to correlate findings with the disease course Methods: Patients with GCA and US defined LV vasculitis were scheduled semiannually for clinical and laboratory assessment as well as US of the temporal (TA), vertebral (VA), carotid (common, internal, external), subclavian (SA), axillary (AXA), deep (DFA), superficial (SFA) and common (CFA) femoral, and popliteal arteries (PA). US findings were classified as normal, moderate or marked vessel wall thickening. Results: From 42 patients (16 male) with a median age of 75 years at diagnosis 28 had typical vessel wall thickening in the temporal artery and in at least one LV segment and 14 in the LV only. The following vessels (marked/moderate) were most often involved: PA in 11/21, SFA in 13/20, AxA in 14/5, SA in 8/13 patients respectively. A reduction of the vessel wall thickening in the temporal artery during follow-up was found in 79% of patients after in median 7 months, with bilateral normalisation in 10 patients after in median 13 months. In contrast 55% had no, 43% a partial and only one patient a complete reduction of thickening of all LV walls during follow-up. From initially marked supra-aortic LV segments 35% were moderate and 16% normal and from initially moderate LV 13% were normal at 1 year FU. From initially marked infra-aortic LV segments 36% were moderate and 3% normal and from initially moderate 10% were normal at 1 year FU. Progression of vessel wall thickening in the LV during FU was seen in a total of 3 patients, in 2 of those, a clinical relapse of GCA was diagnosed one respectively 2 months before US. There was no difference between patients with reduction of the vessel wall thickening and without during follow-up in respect to clinical parameters (relapse rate over the observation time, cumulative steroid dose after one year). Conclusions: Regression of US morphological documented thickening of LV in patients with GCA is rare despite clinical remission. US remains sensitive for the diagnosis of LVV long after treatment initiation. Most plasticity is seen in the TA and more rarely in the supra-aortic segments. Disclosure of Interest: None declared